Pengaruh Model Resource Based Learning Berbantuan Microsite Terhadap Hasil Belajar Ditinjau Dari Motivasi Belajar Siswa - Adilah, Gina Putri; Utaya, Sugeng; Suharto, Yusuf (Jayapangus Press, 2025)
Various problems of decreasing geography learning outcomes such as lack of geography literacy, inadequate teaching, and lack of student learning motivation are problems that need to be followed up on improving geography learning outcomes and student learning motivation. The purpose of this research is to analyze the effect of Resource Based Learning model assisted by Microsite on geography learning outcomes and the interaction of Resource Based Learning model assisted by Microsite between geography learning outcomes and student learning motivation. This research used quantitative approach with Quasi Experimental design. The research subjects were X social studies students at SMAN 1 Purwoharjo in the 2023/2024 school year, with a sample of 105 students divided into experimental and control groups using Purpose sampling technique. Class selection was determined in the experimental class is X 6 and control class X 7. Data collection was done through geography learning outcomes test, learning motivation questionnaire, and learning observation. Data were analyzed using two-way ANOVA with a significance level of 5%. The results showed (1) there is a significant effect of Resource Based Learning model assisted by Microsite on geography learning outcomes; (2) there is a significant interaction of Resource Based Learning model assisted by Microsite between geography learning outcomes and student learning motivation. The Resource Based Learning model assisted by Microsite is effective because the learning is student-centered in meeting the needs and convenience in the learning process. The Microsite-assisted Resource Based Learning model makes it easier for students to be independent and flexible in learning outside of class hours. The Microsite-assisted Resource Based Learning model can optimize the interactive learning process and collaboration between students.